Las macroreglas como estrategia para mejorar el nivel de elaboración de resúmenes de textos expositivos en los estudiantes del vi ciclo - Vásquez Prado, Gonzalo (2021)
The present work entitled: “Macro-rules strategy proposal to improve the level of competence of summary development of various written texts types of VI cycle students”, presents a design of a learning lesson, which develops the capacity to identify the topic, ideas and the purpose of the text, using the Macro-rules and how to elaborate summaries. According to the theorical support, the main contributions of the different authors and MINEDU documents have been taking into consideration both for the teaching practice management and for the communication area development. This point of reference has allowed to support the collected information and also to give support to teachers in their pedagogical job. For the pedagogical support it had been characterized for a reflection about the methodology used in the text comprehension in the learning and teaching process, which is related to a situational approach. It is also assumed the cognitive approach is a basis of pedagogical practice, competence assessment and formative assessment. As a result, the work is based on the development of the learning lesson under competences approach, in this way it achieves the importance of teachers planning, identify meaningful situations according to context and the transversal approaches, the management of different learning strategies as well. All of these, according to the competences, capacities, and performance of the communication area in the secondary level.